Pemberdayaan Masyarakat dalam Penanggulangan Bencana di Desa Karanggadung, Kecamatan Petanahan, Kabupaten Kebumen - Totok Ari Setyanto; Sri Suwitri; Kismartini Kismartini (Asosiasi Ilmuwan Administrasi Negara (AsIAN), 2026)
Previous studies on community-based disaster risk reduction have mainly focused on program implementation, community participation, or institutional capacity, while limited attention has been given to empowerment processes through integrated enabling, empowering, and protecting dimensions in coastal disaster-prone villages. This study analyzes community empowerment in disaster management in Karanggadung Village, Petanahan District, Kebumen Regency, and identifies its supporting and inhibiting factors. A qualitative descriptive case study approach was employed. Data were collected through in-depth interviews with key informants from the village government, Disaster Risk Reduction Forum, Regional Disaster Management Agency, community representatives, volunteers, and vulnerable groups, supported by observation and document analysis. The findings show that empowerment has developed through risk information, disaster education, institutional strengthening, training, community participation, local innovation, vulnerable group protection, and transparent disaster assistance information. Supporting factors include participatory village leadership, the active role of the Disaster Risk Reduction Forum, collaboration with government and volunteer networks, and mutual cooperation. Inhibiting factors include limited budgets, low training continuity, limited information technology access, and weak integration of disaster risk reduction into village planning. This study contributes to public administration by offering an integrated empowerment framework for strengthening coastal community resilience.